Hydraulic Analysis of Different Cross Sections and Channel Covering Types (Proceedings of Faculty of Civil Engineering, 2019)
This paper presents hydraulic analysis of flow in channels under the influence of various cross-sections and type of covering of the channel. During the analysis of different cross sections, a hydraulic design was made for uniform stationary flow for the triangular, rectangular, trapezoidal and semicircular cross-sectional shape of the channel. First performed hydraulic analysis established that the semicircular cross-section of the channel is the most favorable in terms of flow. In the second hydraulic analysis, various types of covering of the channel were observed and a hydraulic design for uniform stationary flow was carried out in order to observe different channel coverings, i.e. the coefficient of roughness. The analysis showed that higher coefficients of roughness give a smaller flow in the channel and smaller coefficients of roughness give a higher flow in the channel. In this case, when dimensioning the channel or the hydraulic design, the appropriate cross section of the channel and the type of covering of the channel should be taken into consideration so that the dimensioned channel is most favorable in terms of smaller hydraulic losses and greater flow in the channel.
Keywords: channels; coefficient of roughness; hydraulic analysis; roughness of channel; channel cross-section; flowability of channels